Implementation Of Dominus Litis Religious Court In Indonesia - Hazar Kusmayanti; Anita Afriana; Dede Kania (Universitas Lampung, 2025)
The principle of judicial passivity is a fundamental tenet in Indonesian civil procedural law; however, judges are not passive throughout all trial stages and may adopt an active role at times. Similarly, judges in religious courts—judicial bodies under the Supreme Court—have begun to apply the principle of active judging. This raises the question of whether such judicial activism conflicts with civil procedural regulations in Indonesia. This paper examines the implementation of the Dominus Litis principle (active judge) within Religious Courts by analyzing various judicial decisions and considerations. Employing a qualitative juridical descriptive approach, the research finds that panels of judges in Religious Courts actively apply the Dominus Litis principle during conciliation, evidence assessment, legal counseling, and the mobile court program.